Do-Over - Deriso, Christine Hurley (New York Delacorte Press, 2006)
Seventh-grader Elsa moves to a new town and starts a new school where, with the help of her recently deceased mother and a magic locket that allows her to redo the last ten seconds in any situation, she attempts to become popular.
5 - 9
Keywords: Conduct of life - Fiction; Popularity - Fiction; Magic - Fiction; Grief - Fiction; Schools - Fiction